Pengaruh Perbedaan Ukuran Fragmen dan Metode Transplantasi Terhadap Pertumbuhan Karang Pocillopora damicornis di Teluk Awur, Jepara - Prameliasari, Tiwi Ajeng; Munasik, Munasik; Wijayanti, Diah Permata (977-2407769)
Coral transplantation is one of culture methods by cutting a part of coral colony to be planted in the other place. Many kinds of coral transplantation methods have been applied such as electrolysis methods and coral transplantation using concrete substrate. Transplantation method used 2 factor, they are initial size (3 and 5 cm) and transplantation media method (used line and cement). The highest survival rates was shown by the fragment that were transplanted using hanging method on rope with an initial size of fragments was 5 cm. The survival rates of the transplants achieved 100%. While the rest of transplants both with the initial size 3 and 5 cm of substrate cement method and hanging on rope with the initial size 3 cm, only 83% of coral transplant were survived due to some fragments were dead and or disappeared. The highest growth rate of coral transplants to monthly look at the string method with fragment size is 3 cm (0.56 cm / month). While the lowest rate of coral growth seen in the string method with fragment size is 5 cm (0.43 cm / month). The growth of coral transplants to data analysis using SPSS 16 indicates no significant difference (p> 0.05) at the rate of coral growth on initial size differences and transplantation methods used and there is no interaction between initial size and method of transplantation.